2011
DOI: 10.1615/critrevoncog.v16.i1-2.120
|View full text |Cite
|
Sign up to set email alerts
|

Gadd45 Stress Sensors in Malignancy and Leukemia

Abstract: Gadd45 proteins, including Gadd45a, Gadd45b and Gadd45g, have been implicated in stress signaling in response to physiological and environmental stress, including oncogenic stress, which can result in cell cycle arrest, DNA repair, cell survival, senescence, and apoptosis. The function of Gadd45 as a stress sensor is mediated via a complex interplay of physical interactions with other cellular proteins implicated in cell cycle regulation and the response of cells to stress, notably PCNA, p21, cdc2/cyclinB1, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
112
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(117 citation statements)
references
References 74 publications
1
112
0
Order By: Relevance
“…The enhanced expression of GADD45G in aged HSCs, and the finding that aged GADD45G-depleted HSCs show an increased self-renewal and accumulation , may indicate a role of GADD45G in HSC life span control. Further, the epigenetic inactivation of Gadd45g in many malignancies explains the inability of tumor cells to terminally differentiate (Liebermann et al, 2011). Further studies are warranted to utilize the GADD45G-mediated pathway to therapeutically switch misregulated self-renewal in cancer-initiating cells into differentiation.…”
Section: Stem Cell Reportsmentioning
confidence: 99%
See 1 more Smart Citation
“…The enhanced expression of GADD45G in aged HSCs, and the finding that aged GADD45G-depleted HSCs show an increased self-renewal and accumulation , may indicate a role of GADD45G in HSC life span control. Further, the epigenetic inactivation of Gadd45g in many malignancies explains the inability of tumor cells to terminally differentiate (Liebermann et al, 2011). Further studies are warranted to utilize the GADD45G-mediated pathway to therapeutically switch misregulated self-renewal in cancer-initiating cells into differentiation.…”
Section: Stem Cell Reportsmentioning
confidence: 99%
“…GADD45G caught our interest because of its role as DNA-damage response and tumor suppressor gene that is epigenetically silenced in many malignancies (Liebermann et al, 2011). Moreover, GADD45G is upregulated in LT-HSCs of aged mice with reduced reconstitution ability (Rossi et al, 2005), and small hairpin RNA (shRNA)-mediated knockdown of GADD45G selected for aged HSCs with higher self-renewal potential .…”
Section: Introductionmentioning
confidence: 99%
“…GADD45 mediates diverse cellular processes, such as DNA repair, apoptosis, cell cycle arrest and senescence (15,16). The GADD45 proteins also function in gene activation, by promoting DNA demethylation and MAPK signaling.…”
Section: ) Do Gaadd45 Family Proteins Contribute To the Dna Demethylmentioning
confidence: 99%
“…Both of these metabolites interact with DNA to form DNA adducts and induce errors during DNA and RNA synthesis. Previous studies showed that VC exposure physiological stress, as well as to have a role in development and carcinogenesis [9]. GADD45A induction following DNA damage is rapid, transient and dose-dependent.…”
Section: Introductionmentioning
confidence: 96%